PENGARUH KUALITAS PELAYANAN, TEKNOLOGI INFORMASI & KEMUDAHAN PENGGUNA DENGAN TERHADAP PELAPORAN PAJAK E-FILING - Dipateruna Teruna Awaludin; Hasanudin Hasanudin; Yolif Alfitriani (JURNAL REKAYASA INFORMASI, 2023)
ABSTRACT This study aims to analyze the influence of Service Quality. Information Technology, and User Ease of Tax Reporting e-Filing. This study uses primary data obtained from respondents' answers to the questionnaire used in the study. The sample of this research is 100 taxpayers at the Depok Sawangan Primary Tax Service Office. Sampling technique using purposive sampling. Methods of data analysis using Descriptive Statistics, Data Quality Test, Classical Assumption Test, and Hypothesis Testing which consists of the Simple Regression Analysis Method, and the Coefficient of Determination, F Test, and t Test. The results show that Service Quality has a significant and positive effect on Tax Reporting e-Filing. Information Technology has a significant and positive effect on Tax Reporting e-Filing. User Ease has a significant and positive effect on Tax Reporting e-Filing. Keywords : Service Quality. Information Technology, User Ease and Tax Reporting e-Filing.